1999
DOI: 10.1046/j.1365-2761.1999.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular products from an isolate of Vibrio harveyi recovered from diseased post‐larval Penaeus vannamei (Bonne)

Abstract: Vibrio harveyi recovered from diseased post‐larval Penaeus vannamei produced a thermostable exotoxin, which was lethal to Dublin Bay prawns, Nephrops norvegicus L., when injected intramuscularly. The extracellular products (ECPs) concentrated from tryptone soya broth supplemented with 1% (w/v) sodium chloride or from cellophane overlays on marine 2216E agar with incubation at 15, 22 and 27 °C were toxic, with the lethal dose 50% of the crude ECPs estimated to be 4.4 μgprotein prawn−1. Proteolytic, haemolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
2
39
2
Order By: Relevance
“…Several isolates studied here showed moderate to strong activity for proteases and phospholipases, and these activities gave significant positive correlation with naupliar mortality. Other authors have also observed high enzyme activity in virulent Vibrio harveyi strains isolated from mollusks (Borrego et al 1996) and from shrimps and fishes (Liu et al 1996b, Montero & Austin 1999, Zhang & Austin 2000.…”
Section: Discussionmentioning
confidence: 85%
“…Several isolates studied here showed moderate to strong activity for proteases and phospholipases, and these activities gave significant positive correlation with naupliar mortality. Other authors have also observed high enzyme activity in virulent Vibrio harveyi strains isolated from mollusks (Borrego et al 1996) and from shrimps and fishes (Liu et al 1996b, Montero & Austin 1999, Zhang & Austin 2000.…”
Section: Discussionmentioning
confidence: 85%
“…The putative toxic virulence factors contained in the PFs40 and the FPLC fraction from Vibrio penaeicida Strain AM101 were subjected to different neutralizing treatments before being injected intra-muscularly into shrimp (25 µl ind. ), aprotinin (4 µg ml -1 for 1 h at 37°C), CuCl 2 (5 mM for 30 min at 25°C), and trans-epoxysuccinyl-L-leucylamido (4-guanidino) butane or E-64 (0.5 mg ml -1 for 1 h at 37°C) , Montero & Austin 1999. Control shrimp groups were injected with one of the chemical inhibitors alone at the same concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…show great variation in terms of pathogenicity associated with host species, developmental stage, bacterial dose, bacteria species and particular strains, and exposure time and stress (Lightner 1996, Saulnier et al 2000a, Aguirre-Guzmán et al 2001. Different Vibrio extracellular products (ECP) have been identified and proposed as putative virulence factors in the species pathogenic to shrimp (Liu et al 1996, 1999a,b, Chen et al 1999, Harris & Owens 1999, Montero & Austin 1999. A thermo-labile cytotoxic factor was detected in the ECP from V. penaeicida, which produces 100% mortality in juvenile Litopenaeus stylirostris (Goarant et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that vibrio bacteria including V. alginolyticus, V. cholerae, V. parahaemolyticus, V. vulnificus, V. mimicus, and V. harveyi are the important pathogens, as these are always isolated from diseased L. vannamei (Lighter, 1993;Vandenberghe et al, 1999;Montero & Austin, 1999). Bacterial pathogens can cause problems that range from growth retardation to sporadic mortalities and mass mortalities of shrimp.…”
Section: Introductionmentioning
confidence: 99%